Digital pocket book integrated with virtual laboratory of quantities, unit, and measurement for elementary school teacher education students - Saidatun Navisah; Ahmad Ma'ruf Nur Salabi; Desy Fitriani; Jane Arantika (HAFECS PRESS, 2026)
The teaching of material on quantities, units, and measurements at the university level, particularly for students in Elementary School Teacher Education programs, still largely relies on conventional methods and printed textbooks with limited visualizations. Additionally, laboratory practical sessions often face challenges due to limited laboratory facilities. This situation highlights the importance of developing technology-based learning media that are integrated and support self-directed learning as well as optimal conceptual understanding. The objective of this study is to describe the validity of a digital pocketbook integrated with a virtual laboratory for the subject matter of quantities, units, and measurements for Primary School Teacher Education Students. This type of research is Research and Development using the 4D model (Define, Design, Develop, and Disseminate). The research subjects were six validators. Based on the results and discussion, the digital handbook integrated with the virtual laboratory falls into the highly valid category, with an average score of 4.56. Therefore, this handbook is highly suitable for use as an innovative digital learning medium that supports interactive, self-directed, and meaningful learning of concepts related to quantities, units, and measurements for elementary school teacher education students. Abstrak. Pembelajaran materi besaran, satuan, dan pengukuran di tingkat universitas khususnya bagi mahasiswa Program Studi Pendidikan Guru Sekolah Dasar, masih banyak menggunakan metode konvensional dan buku cetak dengan visualisasi yang terbatas. Selain itu, pelaksanaan praktikum kerap mengalami kendala akibat keterbatasan fasilitas laboratorium. Kondisi ini mengindikasikan pentingnya pengembangan media pembelajaran berbasis teknologi yang terintegrasi dan mendukung pembelajaran mandiri serta pemahaman konsep yang lebih optimal. Adapun tujuan dari penelitian ini adalah untuk mendeskripsikan validitas buku saku digital yang terintegrasi dengan laboratorium virtual pada materi besaran, satuan, dan pengukuran. Jenis penelitian ini adalah penelitian pengembangan (Research and Development) dengan model 4D (Define, Design, Develop, dan Disseminate). Subjek penelitian adalah enam orang validator. Berdasarkan hasil dan pembahasan menunjukkan bahwa buku saku digital terintegrasi laboratorium virtual berada pada kategori sangat valid, dengan skor rata-rata 4,56. Dengan demikian, buku saku ini sangat layak digunakan sebagai media pembelajaran digital inovatif yang mendukung pembelajaran konsep besaran, satuan, dan pengukuran secara interaktif, mandiri, dan bermakna bagi mahasiswa Pendidikan Guru Sekolah Dasar.